Comparative efficacy of acupuncture point stimulation treatments for dialysis patients with uremic pruritus: a systematic review and network meta-analysis - Lu, Po-Hsuan; Chuo, Hui-En; Chiu, Ling-Ya; Lai, Chien-Cheng; Wang, Jen-Yu; Lu, Ping-Hsun (Frontiers in Neurology, 2024)
Background Uremic pruritus (UP) is a common complication of chronic kidney disease that causes sleep disturbances and increases all-cause mortality. Currently, the first-line medications for UP exhibit inadequate pruritus control with adverse effects. Various acupuncture point stimulation treatments (APSTs) have been shown to be effective as adjuvant therapies in UP, and a network meta-analysis can offer relative efficacy estimates for treatments for which head-to-head studies have not been performed. Methods We conducted a random-effects network meta-analysis on a consistency model to compare the different APSTs for UP. The primary outcomes were the mean visual analog scale (VAS) score and effectiveness rate (ER). Results The network meta-analysis retrieved 27 randomized controlled trials involving 1969 patients. Compared with conventional treatment alone, combination treatment with acupuncture (mean difference, −2.63; 95% confidence interval, −3.71 to −1.55) was the most effective intervention in decreasing VAS scores, followed by acupoint injection and massage (mean difference, −2.04; 95% confidence interval, −3.96 to −0.12). In terms of the ER, conventional treatment with acupuncture and hemoperfusion (risk ratio, 14.87; 95% confidence interval, 2.18 to 101.53) was superior to other therapeutic combinations. Considering the VAS score and ER, combination treatment with acupoint injection and massage showed benefits in treating UP. Conclusion Our network meta-analysis provided relative efficacy data for choosing the optimal adjuvant treatment for UP. Combined treatment with acupuncture was more effective than conventional treatment only and was the most promising intervention for treating UP. Systematic review registration: PROSPERO (CRD42023425739: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023425739).